Lapatinib combined with letrozole versus letrozole and placebo as first-line therapy for postmenopausal hormone receptor-positive metastatic breast cancer - Johnston, Stephen; Pippen, Jr, John; Pivot, Xavier; Lichinitser, Mikhail; Sadeghi, Saeed; Dieras, Veronique; Gomez, Henry Leonidas; Romieu, Gilles; Manikhas, Alexey; Kennedy, M John; Press, Michael F; Maltzman, Julie; et al. (Journal of clinical oncology, 2009)
Cross-talk between human epidermal growth factor receptors and hormone receptor pathways may cause endocrine resistance in breast cancer. This trial evaluated the effect of adding lapatinib, a dual tyrosine kinase inhibitor blocking epidermal growth factor receptor and human epidermal growth factor receptor 2 (HER2), to the aromatase inhibitor letrozole as first-line treatment of hormone receptor (HR) -positive metastatic breast cancer (MBC). Postmenopausal women with HR-positive MBC were randomly assigned to daily letrozole (2.5 mg orally) plus lapatinib (1,500 mg orally) or letrozole and placebo. The primary end point was progression-free survival (PFS) in the HER2-positive population. Results In HR-positive, HER2-positive patients (n = 219), addition of lapatinib to letrozole significantly reduced the risk of disease progression versus letrozole-placebo (hazard ratio [HR] = 0.71; 95% CI, 0.53 to 0.96; P = .019); median PFS was 8.2 v 3.0 months, respectively. Clinical benefit (responsive or stable disease >or= 6 months) was significantly greater for lapatinib-letrozole versus letrozole-placebo (48% v 29%, respectively; odds ratio [OR] = 0.4; 95% CI, 0.2 to 0.8; P = .003). Patients with centrally confirmed HR-positive, HER2-negative tumors (n = 952) had no improvement in PFS. A preplanned Cox regression analysis identified prior antiestrogen therapy as a significant factor in the HER2-negative population; a nonsignificant trend toward prolonged PFS for lapatinib-letrozole was seen in patients who experienced relapse less than 6 months since prior tamoxifen discontinuation (HR = 0.78; 95% CI, 0.57 to 1.07; P = .117). Grade 3 or 4 adverse events were more common in the lapatinib-letrozole arm versus letrozole-placebo arm (diarrhea, 10% v 1%; rash, 1% v 0%, respectively), but they were manageable. This trial demonstrated that a combined targeted strategy with letrozole and lapatinib significantly enhances PFS and clinical benefit rates in patients with MBC that coexpresses HR and HER2.